The Technology Strategy in Website Communication Media in Improving Business Activities - Muhammad Baiqun Isbahi; Muhammad Mujtaba Mitra Zuana; Elvira Rachma Mariana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
The competition faced by the company is an obstacle to achieving business goals in order to maintain the growth and survival of the company. System Strategic planning of information systems and information technology which refers to business strategy must be adapted to the company's business processes. The process of finding the future application portfolio is preceded by the discovery of business strategy, IS/IT management strategy and Website strategy. This will lead to the acquisition of fast, accurate and up-to-date information that is needed for decision making. The basic capital in the realm of computerized information systems is an innovation better known as electronic computers and the internet. This study tries to dissect the strategy of systems and technology on website communication media in increasing business activities. The use of the literature study method brings together several important studies from the perspective of the world of communication and economics, and will be linked in a more comprehensive manner. The results of the literature study illustrate that the increase in business communication supported by the website cannot be separated from the concept of information quality. A more visible result is a new concept of design management that emphasizes technical to socio-cultural considerations.